Thermal effects on current-related skyrmion formation in a nanobelt - Zhao, Xuebing; Wang, Shasha; Wang, Chao; Che, Renchao (Applied physics letters, 2018)
We report an in-situ Lorentz transmission electron microscopy (LTEM) investigation to study the thermal effects on the generation of magnetic skyrmions within a nanobelt. Under an action of a moderate current pulse, magnetic skyrmions appear even in the temperature range far below the critical temperature and even at zero field. Finite element simulation reveals that the Joule heating plays an essential role in this behavior. Our results also uncover the importance of the cooling conditions in the current-related in situ LTEM research.